The analysis of the effects of financial distress on the top management in the Republic of Serbia - Rađen, Dragana (The European Journal of Applied Economics, 2015)
This study aims to examine the effects of financial distress on top management structures, as well as to identify the factors affecting managerial change in the companies that adopted the reorganization plan during bankruptcy proceedings in the Republic of Serbia for the period 2009-2014. Out of 39 companies that adopted the reorganization plan, the top management change was observed in 21 companies after the bankruptcy filing year, or within two years following the reorganization plan adoption. Research results indicate a strong negative correlation between the company’s liquidity and the probability of change in top management structures, with the impact of other observed factors not being statistically significant.